2022
DOI: 10.1186/s12885-022-10189-z
|View full text |Cite
|
Sign up to set email alerts
|

Obese mammary tumour-bearing mice are highly sensitive to doxorubicin-induced hepatotoxicity

Abstract: Background Breast cancer is a major health burden for women, worldwide. Lifestyle-related risk factors, such as obesity and being overweight, have reached epidemic proportions and contributes to the development of breast cancer. Doxorubicin (DXR) is a chemotherapeutic drug commonly used to treat breast cancer, and although effective, may cause toxicity to other organs. The mechanisms and effects of DXR on hepatic tissue, and the contributing role of obesity, in breast cancer patients are poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Regardless of the exact mechanism, the observed reduction in hepatic phenylalanine and tyrosine levels could have important implications for cancer treatment, particularly for breast cancer patients who have a high incidence of AIH [ 9 ]. On the one hand, these two metabolites could potentially serve as biomarkers for predicting the development of AIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the exact mechanism, the observed reduction in hepatic phenylalanine and tyrosine levels could have important implications for cancer treatment, particularly for breast cancer patients who have a high incidence of AIH [ 9 ]. On the one hand, these two metabolites could potentially serve as biomarkers for predicting the development of AIH.…”
Section: Discussionmentioning
confidence: 99%
“…Treating patients receiving anthracyclines who develop hepatotoxicity requires a solid understanding of the toxicity mechanism. Previous studies have shown significant structural abnormalities (e.g., hepatocyte vacuolation and focal necrosis) and various Pharmaceuticals 2023, 16, 797 2 of 13 biochemical alterations (e.g., elevated levels of serum aminotransferases and free radicals) in the livers of animal models treated with DOX [9,10]. The molecular insight into AIH indicates a key role of oxidative stress through the production of reactive oxygen species (ROS), which occurs during the hepatic metabolism of anthracyclines [11].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the concentration of the chondroitin fraction of glycosaminoglycans in the alcohol hepatitis group may be a consequence of a decrease in decorin content and a sign of the inflammatory process in the liver (Li et al, 2023). An increase in the concentration of the chondroitin fraction of glycosaminoglycans in the liver in injection of doxorubicin during alcoholic hepatitis group may be a sign of the combination of toxic effects of these substances and threaten the development of liver fibrosis (Dudás et al, 2001;Sedeman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%